Solving The Shortage of Raw Material in Mayora Group - Evelyn, Evelyn; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2014)
Abstract-Increase of sales from one period to another. One reason that causes Mayora’s sales to be increased is the increased population, followed by the expansion that the company has done before. Mayora products cover a range of coffee, chocolate, candy, instant food, biscuit, wafer, and beverage. Mayora group consists of 5 subsidiary companies and one distribution center. Currently, Mayora is facing is the problem in raw material which always in the shortage condition. The availability of raw material for a big class of company like Mayora will be a potential problem faced by the company.There are some factors that influence the shortage of raw material which are the market price fluctuation, availability or infinity, growth for customers, the risks leading from supplying the raw material, decreased stock level, quality, imbalance production with the capacity, and economic downturn or inflation. Several theories are used in other to help justify the position of Mayora in the market, consist of: definition of raw material and commodity, five Porter forces, Fine et al, Kraljic’s framework, and Marshall L Fisher. By using those theories, the situation of Mayora business can be clearly defined and the writer is being able to justify six factors that influence the shortage of raw material in the real condition, they are: the amount of raw material consumed, high bargaining power of supplier, failure in harvest season, suppliers’ interest, delivery time, and seasonal trend. After doing root cause analysis and making the fishbone diagram, then the two root causes that are going to be examined is chosen, which are no change in Mayora’s production capacity, and only few competitive and competent supplier. Based on these two root causes that have been defined, some alternatives is chosen in other to solve the problem. Then, the analytic hierarchy process (AHP) is used to determine which solution to implement. After the AHP calculation, the solutions of optimizing the job of sales team in doing forecast and strategic partnering with local farmers will be chosen. The detail of implementation in terms of steps, resources (time, money, and people) required will be explained further.Keywords: raw material, supplier, shortage, forecast, partnering